Antioxidant and Tyrosinase Inhibitor Activities of Methanol Extracts of Acacia mangium - Rita K Sari; Rahmi Utami; Irmanida Batubara; Anne Carolina; Salina Febriany (Jurnal Ilmu dan Teknologi Kayu Tropis, 2015)
Active compounds utilization of its extractives for cosmetic products increase the value added of mangium tree. The purpose of this study was to determine the antioxidant and an inhibitor tirosinase activities of methanol extract of the various parts of mangium tree. Phytochemical properties of the best extract were also anlayzed. Extraction was conducted by soxhletation in methanol for 12 hours. The antioxidant and tyrosinase inhibitory activities of the extracts were tested in vitro to radical of 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging and inhibition to tyrosinase enzyme. The results showed that leave resulted in the highest methanol ectract followed succesively by bark, heartwood, and sapwood the value of 10.7; 4.4; 2.5; and 0.9%, respectively. The highest antioxidant activity was bark extract and followed by leave, heartwood, and sapwood extracts with EC50 values respectively of 8.3; 26.7; 66.9; and 137.9 ppm. Only bark extract which classified as an active tyrosinase inhibitor with IC50 value of 257.8 ppm in the difenolase reaction. The IC50 value of the positive control (kojic acid) was 116.7 ppm. The other extracts relatively inactive as a tyrosinase inhibitor because their IC50 values > 1000 ppm. The qualitative analysis detect the methanol extract of mangium bark as the best extract containing phenolic compounds (phenol hirokinon, flavonoids, and tannins) and alkaloids which were thought to contribute to the high antioxidant and tyrosinase inhibitor activities.Keywords: Acacia mangium, antioxidant, extracts, tyrosinase inhibitor